PENGARUH PERSEPSI EXPRESSIVENESS, MANFAAT, KEMUDAHAN PENGGUNAAN, NORMA SOSIAL DAN PERSEPSI KUALITAS SISTEM TERHADAP NIAT NASABAH MENGGUNAKAN SMS BANKING DENGAN GENDER SEBAGAI VARIABEL MODERASI PADA BANK BRI DI SURABAYA - Rahayu Rahayu (Fakultas Ekonomi Universitas Islam Darul Ulum Lamongan, 2019)
The combination of cellular telephone technology with internet technology lately is increasingly rife discussed. The analysis in this study was criticized that the population was customers who had savings in BRI Surabaya and had not used BRI SMS banking services, with a sample requirement of 100 respondents. The results of the study indicate that the perceived benefits affect the intention to use SMS banking more strongly in men than women. Then the hypothesis is accepted, because it can be seen from the value of the beta coefficient in men the value of the beta coefficient (0.432) is greater than women whose beta coefficient value (0.225). Perceived ease of use affects the intention to use SMS banking more strongly in women than men. Then the hypothesis is accepted, with a beta coefficient value (-0.188) smaller than women whose beta coefficient value (0.286). Social norms affect the intention to use SMS banking more strongly in women than men. Then the hypothesis is rejected, because it can be seen from the value of the beta coefficient, where in men the value of the beta coefficient (0.314) is greater than women whose beta coefficient value (0.191). The perceived quality of the system influences the intention to use SMS banking more strongly in men than in women. Then the hypothesis is rejected, because it can be seen from the value of the beta coefficient, where in men the value of the beta coefficient (0.398) is smaller than women whose beta coefficient value (0.429). This is due to the fact that women in Surabaya are considered more to consider risk, safety and quality